Kyphotic deformity in pott’s spine - Poudel, Sushil (Journal of Kathmandu Medical College, 2014)
Kyphotic deformity is a well-known complication in spinal tuberculosis patients. This deformity, which is seen in 15% of patients treated conservatively, progresses in two phases: Phase I, which includes the changes in the active phase, and Phase II, which includes changes after the disease is cured. Factors influencing deformity progression are severity of the angle before treatment, the level of the lesion, and age of the patient. Adults have an increase less than 30? during the active phase with no additional changes in the healed phase. During the growth spurt of the children, there is worsening of the deformity in 39% (Type I), an improvement in 44% (Type II), and no change in 17% (Type III). Spine-at risk radiologic signs aid in early identification of the children at risk of late progressive deformity. Surgery for preventing deformity must be done earlier rather than later and in patients with severe disease. DOI: http://dx.doi.org/10.3126/jkmc.v2i4.11790 Journal of Kathmandu Medical College Vol. 2, No. 4, Issue 6, Oct.-Dec., 2013 Page: 201-204